Do top management performance attribution patterns matter to subsequent organizational outcomes? A two-country study of attribution in economic crisis. (7th September 2020) - Lehmberg, Derek; Tangpong, Chanchai
Abstract: Top management plays a central role in interpreting the organization's performance and communicating to stakeholders. Management's performance attributions set the tone for accountability and shape organizational climate. However, prior studies of the relationships between attribution patterns and subsequent performance have been limited and reported mixed results. This study extends this literature stream by examining the relationships of four different types of attribution and subsequent performance concurrently and testing them in a two-country sample. We find a significant positive relationship between positive internal attribution and subsequent performance, and reaffirm prior findings on negative external attribution and performance.